2019
DOI: 10.1186/s13098-019-0488-9
|View full text |Cite
|
Sign up to set email alerts
|

Statins and/or fibrates for diabetic retinopathy: a systematic review and meta-analysis

Abstract: Evidence from observational studies have found a relationship between serum cholesterol and diabetic retinopathy (DR). Apart of the assumption that cholesterolemic control has benefits for patients with diabetes with or without retinopathy, the effects of lipid-lowering drugs have not been properly mapped and critically assessed so far. The objective of this study was to evaluate the effects of statins and/or fibrates on prevention and progression of DR. We conducted a Systematic review of randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…These findings have important clinical implications. In a systematic review of randomized controlled clinical trials, the effect of statins on DR was uncertain, but fibrates reduced the incidence of macular edema by 45% ( 28 ). Our results illustrate widespread retinal lipid alterations that span a wide array of lipids representative of metabolic pathways above and beyond the cholesterol synthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have important clinical implications. In a systematic review of randomized controlled clinical trials, the effect of statins on DR was uncertain, but fibrates reduced the incidence of macular edema by 45% ( 28 ). Our results illustrate widespread retinal lipid alterations that span a wide array of lipids representative of metabolic pathways above and beyond the cholesterol synthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…39 Findings on the association between fibrates and DR remain controversial. 6 , 8 , 9 , 40 , 41 Two large clinical trials showed that fenofibrate slowed the progression of DR and reduced the need for laser treatment in type 2 diabetic patients with pre-existing retinopathy, 9 , 40 whereas two real-world observational studies did not find such associations. 6 , 8 The discrepancy between our findings and those of previous studies may be explained by different patient populations, different confounding factors controlled for, and the lack of data on lipid profiles in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that hypertriglyceridemia may be a surrogate marker of DME [ 38 ]. The effects of fibrates and statins vary; however, the certainty of relevant evidence appeared low in a systemic review [ 39 ]. In the Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified-Release Controlled Evaluation (ADVANCE) and its subsequent studies (ADVANCE-on), lower-extremity ulceration or amputation increased the risk of vision-threatening DR [ 40 ].…”
Section: Discussionmentioning
confidence: 99%